TINGKAT KEBAHAGIAAN LANSIA DI PANTI WERDHA - Mare, Agustina Chriswinda Bura; Sukmawati, Ermalynda (STIKES Suaka Insan, 2024)
Happiness is an individual positive emotion that is important for the well-being of the elderly. Feeling happy can help the elderly in overcoming the problems that are being experienced by the elderly. This research is a descriptive study that aims to determine the level of happiness of the elderly in nursing homes. The research was conducted at one of the privately managed Nursing Homes in Surabaya City. The sample selection method used purposive sampling with a total of 102 elderly respondents. Happiness was measured using the Oxford Happiness Questionnaire. The majority of respondents were aged 75-90 years as much as 51%, female as much as 70.6%, and widow or widower marital status as much as 32.4%. The results showed that most respondents' happiness level was very happy as much as 44.1%. To improve the happiness of the elderly in the Nursing Home, it is expected that the Nursing Home can enhance the fulfillment of needs and provide more varied leisure activities.